SeCo2: Secure Cognitive Semantic Communication in 6G-IoT Networks Using Key-Policy Attribute-Based Encryption and Elliptic Curve Cryptography - Sugitha, G.; Vasanthi, R.; Solairaj, A.; Kalpana, A. V. (Radioengineering Society, 2025)
Secure and efficient data transmission is crucial for maintaining seamless system operations and user trust in the rapidly evolving Internet of Things (IoT) environments. However, IoT networks consistently suffer from data integrity breaches, security vulnerabilities at various network layers, and a high computational cost. Bridging the gap between IoT applications and network infrastructure is essential to addressing these issues. This paper introduces SeCo2, a secure cognitive semantic communication framework for 6G-IoT networks. The framework incorporates a blockchain-based system to provide a secure and privacy-preserving data transmission mechanism. Data preprocessing is conducted using the IoT-Sense dataset, and then encryption is done through a hybrid combination of Key-Policy Attribute-Based Encryption (KP-ABE) and Elliptic Curve Cryptography (ECC). Access control and data permissions are implemented via smart contracts to ensure secure transmission. Additionally, a blockchain security layer utilizing Proof of Stake with Fixed Staking Amounts (PoS-FSA) enhances network security and energy efficiency. For further protection of data integrity, tamper-proof provenance logging prevents unauthorized tampering. Experimental results demonstrate ultra-low latency data transmis¬sion (in the microsecond range), with a transmission delay as low as 0.003001 s for data sizes ranging from 1 GB to 50 GB, and a network security rate of 98%, ensuring more reliable and privacy-preserving IoT ecosystems.
Keywords: 6G-IoT; blockchain; cognitive semantic communication; elliptic curve cryptography; key-policy attribute-based encryption